Absorbable hemostatic composite material for resisting inflammation and promoting healing of acute bleeding part as well as preparation method and application of absorbable hemostatic composite material
By combining oxidized nanocellulose with small-molecule natural anti-inflammatory compounds containing hydroxyl groups and chitosan to form a composite material, the shortcomings of oxidized bacterial nanocellulose in antibacterial properties and histocompatibility are solved, and the effects of acute hemostasis, antibacterial and healing are achieved.
Patent Information
- Application Number
- CN202411453879.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-03-07
AI Technical Summary
The existing oxidized bacterial nanocellulose materials have shortcomings in antibacterial properties and histocompatibility, and the hemostatic speed is slow.
Oxidized nanocellulose composite materials are used to form composite materials by hydrogen bonding adsorption or electrostatic self-assembly with small-molecule natural anti-inflammatory compounds containing hydroxyl groups to improve antibacterial and healing properties.
It has achieved acute hemostasis, broad-spectrum antibacterial, promoting wound healing and absorbable in the body, improving the biosafety and clinical application potential of the material.
Smart Images

Figure CN119564912A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of biomedicine, and particularly relates to an absorbable hemostatic composite material for anti-inflammation and promoting healing of acute bleeding sites, and a preparation method and application thereof. Background Art
[0002] The characteristics of ideal hemostatic materials should be good cytocompatibility, short treatment time, no negative impact on the healing process of tissues, minimal inflammatory response, and no increased likelihood of infection. They should also be non-toxic, non-irritating, non-antigenic, soft, breathable, and permeable. Various materials, including collagen, alginate, chitosan, graphene, cellulose, and gelatin, have been shown to be effective in controlling bleeding. However, these products have not been widely used in clinical practice due to the scarcity of raw materials, high preparation costs, and potential infection risks.
[0003] As a reliable biomaterial, bacterial fiber is becoming more and more popular in the biomedical field, especially in wound repair. Bacterial nanocellulose has the characteristics of unique three-dimensional network structure, high mechanical strength and many good biological functionalities. At the same time, bacterial nanocellulose can be obtained in large quantities through simple fermentation technology, with high purity and low purification cost, which undoubtedly has broad biomedical prospects. 2,2,6,6-Tetramethyl-1-piperidin-n-oxyl free radical can form carboxyl groups on the six active hydroxyl groups of the cellulose glycosyl ring to achieve functional modification of bacterial nanocellulose. Oxidized bacterial nanocellulose and oxidized regenerated cellulose are both derivatives of glucose polymers and have the same glucose ring structural units. Similarly, the carboxyl groups in oxidized bacterial nanocellulose cause the local environment pH value around the wound to decrease, which is not conducive to wound healing. At the same time, there is an upper limit to the antibacterial property brought by the carboxyl group, which cannot inhibit microbial infections caused by fungi. In addition, the absorbability of oxidized nanocellulose in the body cannot meet the requirements of complete degradation in a short time. It takes up to 8 weeks for the materials prepared from plant-derived oxidized regenerated cellulose to be completely absorbed in the human body. In order to better improve the performance of oxidized bacterial nanocellulose materials, it is necessary to combine them with other substances that have antibacterial and anti-inflammatory properties.
[0004] At present, in some public or authorized invention patents, natural / synthetic polymer materials or inorganic materials have been used to modify oxidized regenerated cellulose to improve its antibacterial and hemostatic properties. Such as coagulation factors (CN110339391A), collagen (CN105079886A), alginate (CN104013991A) and carbon nanotubes (CN105056284A). The above composite hemostatic materials only partially improve the performance of oxidized regenerated cellulose and will have a negative impact on the bioabsorbable properties of the materials. With the increasing requirements of the medical community in various countries for the hemostatic performance of hemostatic materials, it is imperative to develop materials with better hemostatic effects. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide an absorbable hemostatic composite material for anti-inflammatory and healing of acute bleeding sites, and a preparation method and application thereof, which overcomes the technical problems of weak antibacterial performance, low tissue compatibility and slow hemostasis speed of oxidized bacterial nanocellulose in the prior art.
[0006] The present invention provides an oxidized nanocellulose composite material, which comprises a matrix and a hydroxyl-containing small molecule natural anti-inflammatory compound loaded on the matrix; wherein the matrix is an oxidized nanocellulose nanofiber network, a composite material of an oxidized nanocellulose nanonetwork and chitosan, or a composite material of an oxidized nanocellulose nanonetwork and chitosan aggregated by ammonium persulfate.
[0007] Furthermore, the oxidized nanocellulose composite material is constructed by using oxidized cellulose as a substrate to build a network structure, and then self-assembles with small molecule natural anti-inflammatory compounds containing hydroxyl groups by hydrogen bond adsorption; or by using oxidized cellulose as a substrate to build a network structure and electrostatic self-assembly with chitosan to load small molecule natural anti-inflammatory compounds containing hydroxyl groups; or by using oxidized cellulose as a substrate to build a network structure, using ammonium persulfate to induce chitosan to produce agglomeration, and simultaneously loading small molecule natural anti-inflammatory compounds containing hydroxyl groups by hydrogen bonds and electrostatic interactions.
[0008] Preferably, the oxidized bacterial nanocellulose is a cellulose nano-three-dimensional fiber produced by bacterial fermentation; the hydroxyl-containing small molecule natural anti-inflammatory compound is one or more of gallic acid, salicylic acid, quercetin, kaempferol, apigenin, and resveratrol;
[0009] The molecular weight of the chitosan is 1 kDa-30 kDa.
[0010] The oxidized bacterial nanocellulose is obtained by using bacterial nanocellulose as a substrate, alkali purification, rinsing with deionized water to neutrality, homogenization and oxidation.
[0011] The present invention provides a method for preparing an oxidized nanocellulose composite material, comprising method 1, method 2 or method 3.
[0012] Method 1: adding a hydroxyl-containing small molecule natural anti-inflammatory compound solution to oxidized nanocellulose, performing a mixed assembly reaction, centrifuging and washing, and freeze-drying to obtain an oxidized nanocellulose composite material;
[0013] Method 2: Add chitosan solution to oxidized nanocellulose for mixed adsorption reaction, then add hydroxyl-containing small molecule natural anti-inflammatory compound solution for hydrogen bonding and electrostatic adsorption reaction, centrifuge washing, freeze drying to obtain oxidized nanocellulose composite material;
[0014] Method 3: Add chitosan solution to oxidized nanocellulose for mixed adsorption reaction, then add ammonium persulfate solution to react (aggregate chitosan by adding ammonium persulfate), then add hydroxyl-containing small molecule natural anti-inflammatory compound solution to react hydrogen bonding and electrostatic adsorption reactions, centrifuge and wash, and freeze-dry to obtain an oxidized nanocellulose composite material.
[0015] Preferably, the oxidized nanocellulose in method 1, method 2 or method 3 is oxidized bacterial nanocellulose, which is added to the oxidized bacterial nanocellulose suspension.
[0016] Preferably, the oxidized bacterial nanocellulose suspension (using oxidized cellulose as a substrate to build a network to form a suspension) comprises: breaking up the bacterial nanocellulose membrane by a homogenizer, oxidizing it at room temperature using a TEMPO / NaBr / NaClO mixed oxidation system, centrifuging and washing, and dialyzing.
[0017] The mass ratio of TEMPO:NaBr:NaClO in the TEMPO / NaBr / NaClO mixed oxidation system is (0.01-0.03):(0.05-0.2):(1-3), and the concentration range of bacterial nanocellulose is 0.1wt%-2wt%.
[0018] Preferably, the mass ratio of TEMPO:NaBr:NaClO in the mixed oxidation system is 0.012-0.02:0.1-0.15:1-2, and the concentration of bacterial nanocellulose is 0.5-1.5wt%.
[0019] The degree of carboxyl oxidation in the oxidized bacterial nanocellulose is 10-50wt%, preferably, the degree of carboxyl oxidation is 20-30%.
[0020] The carboxyl content / oxidation degree affects the degradation performance of the material. If the content is too high, it will easily lead to low local pH and affect tissue healing. If the content is too low, the fiber will be difficult to degrade.
[0021] Preferably, the chitosan solution in method 2-3 is a dilute acetic acid aqueous solution of chitosan.
[0022] The centrifugal washing in the method 1-3 is centrifugal rinsing; the centrifugal washing and freeze drying are: centrifugal rinsing, re-dispersing evenly, assembling a mold, and freeze drying.
[0023] Preferably, the solvent of the hydroxyl-containing small molecule natural anti-inflammatory compound solution in methods 1 to 3 is water or ethanol aqueous solution; the concentration of the hydroxyl-containing small molecule natural anti-inflammatory compound solution is 0.1wt%-1wt%; wherein the concentration of the ethanol aqueous solution is 0.1v / v%-1v / v% ethanol aqueous solution.
[0024] Preferably, in methods 1 to 3, the mass ratio of the hydroxyl-containing small molecule natural anti-inflammatory compound to the oxidized bacterial nanocellulose is 1:1-1:5; in methods 2 to 3, the mass ratio of the oxidized bacterial nanocellulose to chitosan is 1:1-3:1; in method 3, the mass ratio of ammonium persulfate to chitosan is 1:1-1:5.
[0025] Preferably, the adding method in methods 1 to 3 is dropwise addition, which is done slowly and regularly;
[0026] Preferably, the reaction time in method 1 is 0.5-6h;
[0027] Preferably, in the method 2, the chitosan solution is added to the oxidized nanocellulose, reacted for 0.5-5 hours, and then the hydroxyl-containing small molecule natural anti-inflammatory compound solution is added, and reacted for 0.5-6 hours;
[0028] Preferably, in the method 3, the chitosan solution is added to the oxidized nanocellulose, reacted for 0.5-5 hours, then the ammonium persulfate solution is added, reacted for 0.5-3 hours, and then the hydroxyl-containing small molecule natural anti-inflammatory compound solution is added, reacted for 0.5-6 hours.
[0029] The present invention provides an application of any of the oxidized nano-cellulose composite materials in preparing hemostatic, antibacterial and healing-promoting materials.
[0030] The invention uses bacterial nanocellulose as a substrate to prepare oxidized bacterial nanocellulose (OBC), and utilizes its high purity and large specific surface area characteristics to accelerate the coagulation process. At the same time, OBC is composited with gallic acid, salicylic acid, quercetin, kaempferol, apigenin and resveratrol through hydrogen bond adsorption and chitosan through electrostatic self-assembly reaction, and ammonium persulfate can be introduced therein to prepare an absorbable composite material with acute hemostasis, antibacterial and healing-promoting functions.
[0031] In the present invention, oxidized bacterial nanocellulose is selectively prepared by using bacterial nanocellulose as a substrate, and then hydrogen bond interaction adsorption is performed with a hydroxyl-containing small molecule natural anti-inflammatory compound; or oxidized bacterial nanocellulose is selectively prepared by using bacterial nanocellulose as a substrate, and then electrostatic adsorption self-assembly is performed with chitosan, and hydrogen bond electrostatic interaction adsorption is performed on the hydroxyl-containing small molecule natural anti-inflammatory compound at the same time; or oxidized bacterial nanocellulose is selectively prepared by using bacterial nanocellulose as a substrate, and then electrostatic adsorption self-assembly is performed with chitosan after ammonium persulfate initiation aggregation, and hydrogen bond electrostatic interaction adsorption is performed on the hydroxyl-containing small molecule natural anti-inflammatory compound at the same time. The composite material obtained by the present invention has high biological safety, and at the same time has the characteristics of acute hemostasis, broad-spectrum antibacterial, promotion of wound healing, and in vivo degradable and absorbable, suitable for hemostasis of acute bleeding such as surgery and substantial organs, and has good market application prospects in the field of biomedical materials.
[0032] Beneficial Effects
[0033] (1) The material of the present invention uses bacterial nanocellulose as a substrate to prepare oxidized bacterial nanocellulose. The cellulose produced by bacterial fermentation is a nanoscale fiber. After being freeze-dried into a sponge, it has a larger specific surface area, porosity and water absorption rate under the same mass, more obvious capillary phenomenon, better hemostatic effect, better biodegradability, and is easier to be absorbed by the human body.
[0034] (2) The present invention utilizes oxidized bacterial nanocellulose and the phenolic hydroxyl groups of hydroxyl-containing small molecule natural anti-inflammatory compounds to undergo hydrogen bond adsorption self-assembly without the need for additional cross-linking agents; at the same time, the addition of hydroxyl-containing small molecule natural anti-inflammatory compounds improves the procoagulant and antibacterial properties of the material.
[0035] (3) The present invention utilizes the chitosan aggregation reaction initiated by ammonium persulfate to fully adsorb hydroxyl-containing small molecule natural anti-inflammatory compounds on the basis of the large specific surface area of oxidized bacterial nanocellulose for self-assembly reaction. The final obtained material has the characteristics of acute hemostasis, antibacterial, healing promotion and absorbability.
[0036] (4) The raw materials of the present invention are all green and environmentally friendly biological materials, do not contain chemicals harmful to the human body, can be prepared into various shapes according to actual conditions and characteristics, are safe and environmentally friendly, and can be rapidly degraded in the environment after being discarded. They can be used as a functional material with good performance and green and environmental protection.
[0037] (5) The preparation method of the present invention is simple and easy to implement, has high composite efficiency, will not damage the original structure of the synthesized substance, can be industrially produced, and has good market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is a schematic diagram of the preparation process of the present invention;
[0039] Figure 2 The absorbable hemostatic composite product diagrams prepared in Examples 1-4; 1-4 are OBC, OBC / GA, OBC / GA / CS and OBC / GA / CS-APS, respectively;
[0040] Figure 3 is a scanning electron microscope image of the product in Examples 1-4;
[0041] Figure 4 is the in vitro whole blood coagulation curve of Example 1-19;
[0042] Figure 5 The hemolysis rate test results of Examples 1-19;
[0043] Figure 6 The red blood cell adhesion results and in vivo hemostasis test results of Examples 1-19;
[0044] Figure 7 The results of the animal hemostasis model of Examples 1-4;
[0045] Figure 8 is the blood absorption of the wound of the animal model in Examples 1-4;
[0046] Fig. 9 The hemostasis time of the wound in the animal model of Examples 1-4;
[0047] Fig.10 is the hydroxyl radical scavenging rate of Examples 1-19;
[0048] Fig.11 The results of in vivo degradability and biocompatibility evaluation of Examples 1-4 after subcutaneous embedding in rats for 7 days and 28 days are shown. DETAILED DESCRIPTION
[0049] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0050] Example 1
[0051] (1) KomagataeibacterxylinusATCC 23770 was used as the strain (American Type Culture Bank). After being cultured in a liquid culture medium at a constant temperature for 10 days, the bacterial nanocellulose membrane was taken out and placed in a sodium hydroxide solution. After being treated in a water bath at 80°C for 2 h, it was taken out and rinsed with deionized water. This process was repeated 8 times and then soaked in deionized water until neutral to obtain a bacterial nanocellulose membrane.
[0052] (2) Weigh 300 g of the purified bacterial nanocellulose membrane, cut it into pieces, and then break it up in a high-speed homogenizer to form a bacterial nanocellulose suspension.
[0053] (3) 1L of bacterial nanocellulose suspension (solid content 1%) obtained in step (2) was oxidized at room temperature by TEMPO / NaBr / NaClO mixed oxidation system, with 0.16g of TEMPO and 1.03g of NaBr. 150mL of 10% NaClO solution was added to start the reaction. The pH of the reaction system was maintained at 10±0.5 by dripping 0.5M NaOH solution until no more NaOH solution was consumed, and anhydrous ethanol of the same volume of NaClO was added to terminate the oxidation reaction. The obtained product was centrifuged, rinsed, dialyzed, compounded according to a solid content of 1%, and sterilized by high pressure, and then stored at 4°C. The degree of carboxyl oxidation of the TEMPO-oxidized bacterial nanocellulose suspension was measured by conductivity titration to be 23%.
[0054] (4) freeze-drying the oxidized bacterial nanocellulose suspension obtained in step (3) to finally obtain the oxidized bacterial nanocellulose hemostatic material.
[0055] Example 2
[0056] (1) Komagataeibacterxylinus ATCC 23770 was used as the bacterial strain. After being cultured in a liquid culture medium at a constant temperature for 10 days, the bacterial nanocellulose membrane was taken out and placed in a sodium hydroxide solution. After being treated in a water bath at 80°C for 2 h, it was taken out and rinsed with deionized water. This process was repeated 8 times and then soaked in deionized water until neutral to obtain a bacterial nanocellulose membrane.
[0057] (2) Weigh 300 g of the purified bacterial nanocellulose membrane, cut it into pieces, and then break it up in a high-speed homogenizer to form a bacterial nanocellulose suspension.
[0058] (3) 1L of bacterial nanocellulose suspension obtained in step (2) (solid content of 1%) was oxidized at room temperature by a TEMPO / NaBr / NaClO mixed oxidation system, with 0.16g of TEMPO and 1.03g of NaBr. 150mL of 10% NaClO solution was added to start the reaction. The pH of the reaction system was maintained at 10±0.5 by dropwise addition of 0.5M NaOH solution, and when no more NaOH solution was consumed, anhydrous ethanol of the same volume of NaClO was added to terminate the oxidation reaction. The obtained product was centrifuged, rinsed, dialyzed, compounded according to a solid content of 1%, sterilized by high pressure, and stored at 4°C. The degree of carboxyl oxidation of the TEMPO-oxidized bacterial nanocellulose suspension was measured by conductivity titration to be 23%.
[0059] (4) Weigh 0.5 g of gallic acid and fully dissolve it in 100 mL of deionized water to form a gallic acid aqueous solution with a final concentration of 0.5%. (5) Take 20 mL of the gallic acid aqueous solution prepared in step (4) and add it dropwise to 20 mL of the oxidized bacterial nanocellulose suspension prepared in step (3), stir for 30 minutes, repeatedly centrifuge and rinse the product 3 times, and finally freeze-dry to obtain an oxidized bacterial nanocellulose / gallic acid composite hemostatic material.
[0060] Example 3
[0061] (1) KomagataeibacterxylinusATCC 23770 was used as the strain, and after being cultured in a liquid culture medium at a constant temperature for 10 days, the bacterial nanocellulose membrane was taken out and placed in a sodium hydroxide solution, treated in a water bath at 80°C for 2 hours, taken out, and rinsed with deionized water. This process was repeated 8 times, and then soaked in deionized water until neutral to obtain a bacterial nanocellulose membrane.
[0062] (2) Weigh 300 g of the purified bacterial nanocellulose membrane, cut it into pieces, and then break it up in a high-speed homogenizer to form a bacterial nanocellulose suspension.
[0063] (3) 1L of bacterial nanocellulose suspension (solid content 1%) obtained in step (2) was oxidized at room temperature by TEMPO / NaBr / NaClO mixed oxidation system, with 0.16g of TEMPO and 1.03g of NaBr. 150mL of 10% NaClO solution was added to start the reaction. The pH of the reaction system was maintained at 10±0.5 by dripping 0.5M NaOH solution until no more NaOH solution was consumed, and anhydrous ethanol of the same volume of NaClO was added to terminate the oxidation reaction. The obtained product was centrifuged, rinsed, dialyzed, compounded according to a solid content of 1%, and sterilized by high pressure, and then stored at 4°C. The degree of carboxyl oxidation of the TEMPO-oxidized bacterial nanocellulose suspension was measured by conductivity titration to be 23%.
[0064] (4) Weigh 0.5 g of gallic acid and fully dissolve it in 100 mL of deionized water to form a gallic acid aqueous solution with a final concentration of 0.5%. (5) Weigh 1 g of chitosan (15 kDa) and fully dissolve it in 100 mL of 0.1 M glacial acetic acid aqueous solution to form a chitosan dilute acid solution with a final concentration of 1%.
[0065] (6) According to the mass ratio of oxidized bacterial nanocellulose: chitosan = 2:1, take 10 mL of the chitosan dilute acid solution prepared in step (5) and dropwise add it into the beaker containing 20 mL of the oxidized bacterial nanocellulose suspension in step (3), stirring while adding, and react for 30 minutes.
[0066] (7) Take 20 mL of the gallic acid aqueous solution prepared in step (4) and add it dropwise into 30 mL of the oxidized bacterial nanocellulose suspension prepared in step (6). After reacting for 1 hour, the product is repeatedly centrifuged and rinsed 3 times, and finally freeze-dried to obtain an oxidized bacterial nanocellulose / gallic acid / chitosan composite hemostatic material.
[0067] Example 4
[0068] (1) Komagataeibacterxylinus ATCC 23770 was used as the bacterial strain. After being cultured in a liquid culture medium at a constant temperature for 10 days, the bacterial nanocellulose membrane was taken out and placed in a sodium hydroxide solution. After being treated in a water bath at 80°C for 2 h, it was taken out and rinsed with deionized water. This process was repeated 8 times and then soaked in deionized water until neutral to obtain a bacterial nanocellulose membrane.
[0069] (2) Weigh 300 g of the purified bacterial nanocellulose membrane, cut it into pieces, and then break it up in a high-speed homogenizer to form a bacterial nanocellulose suspension.
[0070] (3) 1L of bacterial nanocellulose suspension (solid content 1%) obtained in step (2) was oxidized at room temperature by TEMPO / NaBr / NaClO mixed oxidation system, with 0.16g of TEMPO and 1.03g of NaBr. 150mL of 10% NaClO solution was added to start the reaction. The pH of the reaction system was maintained at 10±0.5 by dripping 0.5M NaOH solution until no more NaOH solution was consumed, and anhydrous ethanol of the same volume of NaClO was added to terminate the oxidation reaction. The obtained product was centrifuged, rinsed, dialyzed, compounded according to a solid content of 1%, and sterilized by high pressure, and then stored at 4°C. The degree of carboxyl oxidation of the TEMPO-oxidized bacterial nanocellulose suspension was measured by conductivity titration to be 23%.
[0071] (4) Weigh 0.5 g of gallic acid and fully dissolve it in 100 mL of deionized water to form a gallic acid aqueous solution with a final concentration of 0.5%.
[0072] (5) Weigh 1 g of chitosan (15 kDa) and fully dissolve it in 100 mL of 0.1 M glacial acetic acid aqueous solution to form a chitosan dilute acid solution with a final concentration of 1%.
[0073] (6) Weigh 5 g of ammonium persulfate and fully dissolve it in 100 mL of deionized water to form an ammonium persulfate aqueous solution with a final concentration of 5%. (7) According to the mass ratio of oxidized bacterial nanocellulose: chitosan = 2:1, take 10 mL of the chitosan dilute acid solution prepared in step (5) and dropwise add it into the beaker containing 20 mL of the oxidized bacterial nanocellulose suspension in step (3), stirring while adding, and react for 30 minutes.
[0074] (8) Take 1 mL of the ammonium persulfate aqueous solution prepared in step (6) and add it dropwise to the mixed solution of oxidized bacterial nanocellulose and chitosan in step (7), stirring while adding dropwise, and react for 30 minutes.
[0075] (9) Take 20 mL of the gallic acid aqueous solution prepared in step (4) and add it dropwise into 31 mL of the oxidized bacterial nanocellulose suspension prepared in step (8). After reacting for 1 hour, the product is repeatedly centrifuged and rinsed three times, and finally freeze-dried to obtain an oxidized bacterial nanocellulose / gallic acid / chitosan (ammonium persulfate) composite hemostatic material.
[0076] Example 5
[0077] (1) Komagataeibacterxylinus ATCC 23770 was used as the bacterial strain. After being cultured in a liquid culture medium at a constant temperature for 10 days, the bacterial nanocellulose membrane was taken out and placed in a sodium hydroxide solution. After being treated in a water bath at 80°C for 2 h, it was taken out and rinsed with deionized water. This process was repeated 8 times and then soaked in deionized water until neutral to obtain a bacterial nanocellulose membrane.
[0078] (2) Weigh 300 g of the purified bacterial nanocellulose membrane, cut it into pieces, and then break it up in a high-speed homogenizer to form a bacterial nanocellulose suspension.
[0079] (3) 1L of bacterial nanocellulose suspension obtained in step (2) (solid content is 1%) is oxidized at room temperature using a TEMPO / NaBr / NaClO mixed oxidation system, with 0.16g of TEMPO and 1.03g of NaBr. 150mL of 10% NaClO solution is added to start the reaction. The pH of the reaction system is maintained at 10±0.5 by dripping 0.5M NaOH solution until no more NaOH solution is consumed, and then anhydrous ethanol of the same volume of NaClO is added to terminate the oxidation reaction. The obtained product is centrifuged, rinsed, dialyzed, compounded according to a solid content of 1%, sterilized under high pressure, and stored at 4°C. The degree of carboxyl oxidation of the TEMPO-oxidized bacterial nanocellulose suspension measured by conductivity titration is 23%.
[0080] (4) Take 10 mL of anhydrous ethanol and dilute to 1 L with deionized water to prepare an ethanol-water solution.
[0081] (5) Weigh 0.5 g of salicylic acid and fully dissolve it in 100 mL of the ethanol aqueous solution prepared in step (4) to form a salicylic acid solution with a final concentration of 0.5%.
[0082] (6) Take 20 mL of the salicylic acid solution prepared in step (5) and add it dropwise to 20 mL of the oxidized bacterial nanocellulose suspension prepared in step (3). After reacting for 30 minutes, the product is repeatedly centrifuged and rinsed, and finally freeze-dried to obtain an oxidized bacterial nanocellulose / salicylic acid composite hemostatic material.
[0083] Example 6
[0084] (1) Komagataeibacterxylinus ATCC 23770 was used as the bacterial strain. After being cultured in a liquid culture medium at a constant temperature for 10 days, the bacterial nanocellulose membrane was taken out and placed in a sodium hydroxide solution. After being treated in a water bath at 80°C for 2 h, it was taken out and rinsed with deionized water. This process was repeated 8 times and then soaked in deionized water until neutral to obtain a bacterial nanocellulose membrane.
[0085] (2) Weigh 300 g of the purified bacterial nanocellulose membrane, cut it into pieces, and then break it up in a high-speed homogenizer to form a bacterial nanocellulose suspension.
[0086] (3) 1L of bacterial nanocellulose suspension obtained in step (2) (solid content is 1%) is oxidized at room temperature using a TEMPO / NaBr / NaClO mixed oxidation system, with 0.16g of TEMPO and 1.03g of NaBr. 150mL of 10% NaClO solution is added to start the reaction. The pH of the reaction system is maintained at 10±0.5 by dripping 0.5M NaOH solution until no more NaOH solution is consumed, and then anhydrous ethanol of the same volume of NaClO is added to terminate the oxidation reaction. The obtained product is centrifuged, rinsed, dialyzed, compounded according to a solid content of 1%, sterilized under high pressure, and stored at 4°C. The degree of carboxyl oxidation of the TEMPO-oxidized bacterial nanocellulose suspension measured by conductivity titration is 23%.
[0087] (4) Take 10 mL of anhydrous ethanol and dilute to 1 L with deionized water to prepare an ethanol-water solution.
[0088] (5) Weigh 0.5 g of salicylic acid and fully dissolve it in 100 mL of the ethanol aqueous solution prepared in step (4) to form a salicylic acid solution with a final concentration of 0.5%.
[0089] (6) Weigh 1 g of chitosan (15 kDa) and fully dissolve it in 100 mL of 0.1 M glacial acetic acid aqueous solution to form a chitosan dilute acid solution with a final concentration of 1%.
[0090] (7) According to the mass ratio of oxidized bacterial nanocellulose: chitosan = 2:1, take 10 mL of the chitosan dilute acid solution prepared in step (6) and dropwise add it into the beaker containing 20 mL of the oxidized bacterial nanocellulose suspension in step (3), stirring while adding, and react for 30 minutes.
[0091] (8) Take 20 mL of the salicylic acid solution prepared in step (5) and add it dropwise to 30 mL of the oxidized bacterial nanocellulose suspension prepared in step (7). After reacting for 1 hour, the product is repeatedly centrifuged and rinsed, and finally freeze-dried to obtain an oxidized bacterial nanocellulose / salicylic acid / chitosan composite hemostatic material.
[0092] Example 7
[0093] (1) Komagataeibacterxylinus ATCC 23770 was used as the bacterial strain. After being cultured in a liquid culture medium at a constant temperature for 10 days, the bacterial nanocellulose membrane was taken out and placed in a sodium hydroxide solution. After being treated in a water bath at 80°C for 2 h, it was taken out and rinsed with deionized water. This process was repeated 8 times and then soaked in deionized water until neutral to obtain a bacterial nanocellulose membrane.
[0094] (2) Weigh 300 g of the purified bacterial nanocellulose membrane, cut it into pieces, and then break it up in a high-speed homogenizer to form a bacterial nanocellulose suspension.
[0095] (3) 1L of bacterial nanocellulose suspension obtained in step (2) (solid content is 1%) is oxidized at room temperature using a TEMPO / NaBr / NaClO mixed oxidation system, with 0.16g of TEMPO and 1.03g of NaBr. 150mL of 10% NaClO solution is added to start the reaction. The pH of the reaction system is maintained at 10±0.5 by dripping 0.5M NaOH solution until no more NaOH solution is consumed, and then anhydrous ethanol of the same volume of NaClO is added to terminate the oxidation reaction. The obtained product is centrifuged, rinsed, dialyzed, compounded according to a solid content of 1%, sterilized under high pressure, and stored at 4°C. The degree of carboxyl oxidation of the TEMPO-oxidized bacterial nanocellulose suspension measured by conductivity titration is 23%.
[0096] (4) Take 10 mL of anhydrous ethanol and dilute to 1 L with deionized water to prepare an ethanol-water solution.
[0097] (5) Weigh 0.5 g of salicylic acid and fully dissolve it in 100 mL of the ethanol aqueous solution prepared in step (4) to form a salicylic acid solution with a final concentration of 0.5%.
[0098] (6) Weigh 1 g of chitosan (15 kDa) and fully dissolve it in 100 mL of 0.1 M glacial acetic acid aqueous solution to form a chitosan dilute acid solution with a final concentration of 1%.
[0099] (7) Weigh 5 g of ammonium persulfate and fully dissolve it in 100 mL of deionized water to form an ammonium persulfate aqueous solution with a final concentration of 5%. (8) According to the mass ratio of oxidized bacterial nanocellulose: chitosan = 2:1, take 10 mL of the chitosan dilute acid solution prepared in step (6) and dropwise add it into the beaker containing 20 mL of the oxidized bacterial nanocellulose suspension in step (3), stirring while adding, and react for 30 minutes.
[0100] (9) Take 1 mL of the ammonium persulfate aqueous solution prepared in step (7) and add it dropwise to the mixed solution of oxidized bacterial nanocellulose and chitosan in step (8), stirring while adding dropwise, and react for 30 minutes.
[0101] (10) Take 20 mL of the salicylic acid ethanol aqueous solution prepared in step (5) and add it dropwise to 31 mL of the oxidized bacterial nanocellulose suspension prepared in step (9). After reacting for 1 hour, the product is repeatedly centrifuged and rinsed, and finally freeze-dried to obtain an oxidized bacterial nanocellulose / salicylic acid / chitosan (ammonium persulfate) composite hemostatic material.
[0102] Example 8
[0103] (1) Komagataeibacterxylinus ATCC 23770 was used as the bacterial strain. After being cultured in a liquid culture medium at a constant temperature for 10 days, the bacterial nanocellulose membrane was taken out and placed in a sodium hydroxide solution. After being treated in a water bath at 80°C for 2 h, it was taken out and rinsed with deionized water. This process was repeated 8 times and then soaked in deionized water until neutral to obtain a bacterial nanocellulose membrane.
[0104] (2) Weigh 300 g of the purified bacterial nanocellulose membrane, cut it into pieces, and then break it up in a high-speed homogenizer to form a bacterial nanocellulose suspension.
[0105] (3) 1L of bacterial nanocellulose suspension obtained in step (2) (solid content is 1%) is oxidized at room temperature using a TEMPO / NaBr / NaClO mixed oxidation system, with 0.16g of TEMPO and 1.03g of NaBr. 150mL of 10% NaClO solution is added to start the reaction. The pH of the reaction system is maintained at 10±0.5 by dripping 0.5M NaOH solution until no more NaOH solution is consumed, and then anhydrous ethanol of the same volume of NaClO is added to terminate the oxidation reaction. The obtained product is centrifuged, rinsed, dialyzed, compounded according to a solid content of 1%, sterilized under high pressure, and stored at 4°C. The degree of carboxyl oxidation of the TEMPO-oxidized bacterial nanocellulose suspension measured by conductivity titration is 23%.
[0106] (4) Take 10 mL of anhydrous ethanol and dilute to 1 L with deionized water to prepare an ethanol-water solution.
[0107] (5) Weigh 0.5 g of quercetin and fully dissolve it in 100 mL of the ethanol aqueous solution prepared in step (4) to form a quercetin solution with a final concentration of 0.5%.
[0108] (6) Take 20 mL of the quercetin solution prepared in step (5) and add it dropwise into 20 mL of the oxidized bacterial nanocellulose suspension prepared in step (3). After reacting for 30 minutes, the product is repeatedly centrifuged and rinsed, and finally freeze-dried to obtain an oxidized bacterial nanocellulose / quercetin composite hemostatic material.
[0109] Example 9
[0110] (1) Komagataeibacterxylinus ATCC 23770 was used as the bacterial strain. After being cultured in a liquid culture medium at a constant temperature for 10 days, the bacterial nanocellulose membrane was taken out and placed in a sodium hydroxide solution. After being treated in a water bath at 80°C for 2 h, it was taken out and rinsed with deionized water. This process was repeated 8 times and then soaked in deionized water until neutral to obtain a bacterial nanocellulose membrane.
[0111] (2) Weigh 300 g of the purified bacterial nanocellulose membrane, cut it into pieces, and then break it up in a high-speed homogenizer to form a bacterial nanocellulose suspension.
[0112] (3) 1L of bacterial nanocellulose suspension obtained in step (2) (solid content is 1%) is oxidized at room temperature using a TEMPO / NaBr / NaClO mixed oxidation system, with 0.16g of TEMPO and 1.03g of NaBr. 150mL of 10% NaClO solution is added to start the reaction. The pH of the reaction system is maintained at 10±0.5 by dripping 0.5M NaOH solution until no more NaOH solution is consumed, and then anhydrous ethanol of the same volume of NaClO is added to terminate the oxidation reaction. The obtained product is centrifuged, rinsed, dialyzed, compounded according to a solid content of 1%, sterilized under high pressure, and stored at 4°C. The degree of carboxyl oxidation of the TEMPO-oxidized bacterial nanocellulose suspension measured by conductivity titration is 23%.
[0113] (4) Take 10 mL of anhydrous ethanol and dilute to 1 L with deionized water to prepare an ethanol-water solution.
[0114] (5) Weigh 0.5 g of quercetin and fully dissolve it in 100 mL of the ethanol aqueous solution prepared in step (4) to form a quercetin solution with a final concentration of 0.5%.
[0115] (6) Weigh 1 g of chitosan (15 kDa) and fully dissolve it in 100 mL of 0.1 M glacial acetic acid aqueous solution to form a chitosan dilute acid solution with a final concentration of 1%.
[0116] (7) According to the mass ratio of oxidized bacterial nanocellulose: chitosan = 2:1, take 10 mL of the chitosan dilute acid solution prepared in step (6) and dropwise add it into the beaker containing 20 mL of the oxidized bacterial nanocellulose suspension in step (3), stirring while adding, and react for 30 minutes.
[0117] (8) Take 20 mL of the quercetin solution prepared in step (5) and add it dropwise into 30 mL of the oxidized bacterial nanocellulose suspension prepared in step (7). After reacting for 1 hour, the product is repeatedly centrifuged and rinsed, and finally freeze-dried to obtain an oxidized bacterial nanocellulose / quercetin / chitosan composite hemostatic material.
[0118] Example 10
[0119] (1) Komagataeibacterxylinus ATCC 23770 was used as the bacterial strain. After being cultured in a liquid culture medium at a constant temperature for 10 days, the bacterial nanocellulose membrane was taken out and placed in a sodium hydroxide solution. After being treated in a water bath at 80°C for 2 h, it was taken out and rinsed with deionized water. This process was repeated 8 times and then soaked in deionized water until neutral to obtain a bacterial nanocellulose membrane.
[0120] (2) Weigh 300 g of the purified bacterial nanocellulose membrane, cut it into pieces, and then break it up in a high-speed homogenizer to form a bacterial nanocellulose suspension.
[0121] (3) 1L of bacterial nanocellulose suspension obtained in step (2) (solid content is 1%) is oxidized at room temperature using a TEMPO / NaBr / NaClO mixed oxidation system, with 0.16g of TEMPO and 1.03g of NaBr. 150mL of 10% NaClO solution is added to start the reaction. The pH of the reaction system is maintained at 10±0.5 by dripping 0.5M NaOH solution until no more NaOH solution is consumed, and then anhydrous ethanol of the same volume of NaClO is added to terminate the oxidation reaction. The obtained product is centrifuged, rinsed, dialyzed, compounded according to a solid content of 1%, sterilized under high pressure, and stored at 4°C. The degree of carboxyl oxidation of the TEMPO-oxidized bacterial nanocellulose suspension measured by conductivity titration is 23%.
[0122] (4) Take 10 mL of anhydrous ethanol and dilute to 1 L with deionized water to prepare an ethanol-water solution.
[0123] (5) Weigh 0.5 g of quercetin and fully dissolve it in 100 mL of the ethanol aqueous solution prepared in step (4) to form a quercetin solution with a final concentration of 0.5%.
[0124] (6) Weigh 1 g of chitosan (15 kDa) and fully dissolve it in 100 mL of 0.1 M glacial acetic acid aqueous solution to form a chitosan dilute acid solution with a final concentration of 1%.
[0125] (7) Weigh 5 g of ammonium persulfate and fully dissolve it in 100 mL of deionized water to form an ammonium persulfate aqueous solution with a final concentration of 5%. (8) According to the mass ratio of oxidized bacterial nanocellulose: chitosan = 2:1, take 10 mL of the chitosan dilute acid solution prepared in step (6) and dropwise add it into the beaker containing 20 mL of the oxidized bacterial nanocellulose suspension in step (3), stirring while adding, and react for 30 minutes.
[0126] (9) Take 1 mL of the ammonium persulfate aqueous solution prepared in step (7) and add it dropwise to the mixed solution of oxidized bacterial nanocellulose and chitosan in step (8), stirring while adding dropwise, and react for 30 minutes.
[0127] (10) Take 20 mL of the quercetin solution prepared in step (5) and add it dropwise into 31 mL of the oxidized bacterial nanocellulose suspension prepared in step (9). After reacting for 1 hour, the product is repeatedly centrifuged and rinsed, and finally freeze-dried to obtain an oxidized bacterial nanocellulose / quercetin / chitosan (ammonium persulfate) composite hemostatic material.
[0128] Embodiment 11
[0129] (1) Komagataeibacterxylinus ATCC 23770 was used as the bacterial strain. After being cultured in a liquid culture medium at a constant temperature for 10 days, the bacterial nanocellulose membrane was taken out and placed in a sodium hydroxide solution. After being treated in a water bath at 80°C for 2 h, the membrane was taken out and rinsed with deionized water. This process was repeated 8 times and then the membrane was soaked in deionized water until neutral to obtain the bacterial nanocellulose membrane.
[0130] (2) Weigh 300 g of the purified bacterial nanocellulose membrane, cut it into pieces, and then break it up in a high-speed homogenizer to form a bacterial nanocellulose suspension.
[0131] (3) 1L of bacterial nanocellulose suspension obtained in step (2) (solid content is 1%) is oxidized at room temperature using a TEMPO / NaBr / NaClO mixed oxidation system, with 0.16g of TEMPO and 1.03g of NaBr. 150mL of 10% NaClO solution is added to start the reaction. The pH of the reaction system is maintained at 10±0.5 by dripping 0.5M NaOH solution until no more NaOH solution is consumed, and then anhydrous ethanol of the same volume of NaClO is added to terminate the oxidation reaction. The obtained product is centrifuged, rinsed, dialyzed, compounded according to a solid content of 1%, sterilized under high pressure, and stored at 4°C. The degree of carboxyl oxidation of the TEMPO-oxidized bacterial nanocellulose suspension measured by conductivity titration is 23%.
[0132] (4) Take 10 mL of anhydrous ethanol and dilute to 1 L with deionized water to prepare an ethanol-water solution.
[0133] (5) Weigh 0.5 g of kaempferol and fully dissolve it in 100 mL of the ethanol aqueous solution prepared in step (4) to form a kaempferol solution with a final concentration of 0.5%.
[0134] (6) Take 20 mL of the kaempferol solution prepared in step (5) and add it dropwise to 20 mL of the oxidized bacterial nanocellulose suspension prepared in step (3). After reacting for 30 minutes, the product is repeatedly centrifuged and rinsed, and finally freeze-dried to obtain an oxidized bacterial nanocellulose / kaempferol composite hemostatic material.
[0135] Example 12
[0136] (1) Komagataeibacterxylinus ATCC 23770 was used as the bacterial strain. After being cultured in a liquid culture medium at a constant temperature for 10 days, the bacterial nanocellulose membrane was taken out and placed in a sodium hydroxide solution. After being treated in a water bath at 80°C for 2 h, it was taken out and rinsed with deionized water. This process was repeated 8 times and then soaked in deionized water until neutral to obtain a bacterial nanocellulose membrane.
[0137] (2) Weigh 300 g of the purified bacterial nanocellulose membrane, cut it into pieces, and then break it up in a high-speed homogenizer to form a bacterial nanocellulose suspension.
[0138] (3) 1L of bacterial nanocellulose suspension obtained in step (2) (solid content is 1%) is oxidized at room temperature using a TEMPO / NaBr / NaClO mixed oxidation system, with 0.16g of TEMPO and 1.03g of NaBr. 150mL of 10% NaClO solution is added to start the reaction. The pH of the reaction system is maintained at 10±0.5 by dripping 0.5M NaOH solution until no more NaOH solution is consumed, and then anhydrous ethanol of the same volume of NaClO is added to terminate the oxidation reaction. The obtained product is centrifuged, rinsed, dialyzed, compounded according to a solid content of 1%, sterilized under high pressure, and stored at 4°C. The degree of carboxyl oxidation of the TEMPO-oxidized bacterial nanocellulose suspension measured by conductivity titration is 23%.
[0139] (4) Take 10 mL of anhydrous ethanol and dilute to 1 L with deionized water to prepare an ethanol-water solution.
[0140] (5) Weigh 0.5 g of kaempferol and fully dissolve it in 100 mL of the ethanol aqueous solution prepared in step (4) to form a kaempferol solution with a final concentration of 0.5%.
[0141] (6) Weigh 1 g of chitosan (15 kDa) and fully dissolve it in 100 mL of 0.1 M glacial acetic acid aqueous solution to form a chitosan dilute acid solution with a final concentration of 1%.
[0142] (7) According to the mass ratio of oxidized bacterial nanocellulose: chitosan = 2:1, take 10 mL of the chitosan dilute acid solution prepared in step (6) and dropwise add it into the beaker containing 20 mL of the oxidized bacterial nanocellulose suspension in step (3), stirring while adding, and react for 30 minutes.
[0143] (8) Take 20 mL of the kaempferol solution prepared in step (5) and add it dropwise to 30 mL of the oxidized bacterial nanocellulose suspension prepared in step (7). After reacting for 1 hour, the product is repeatedly centrifuged and rinsed, and finally freeze-dried to obtain an oxidized bacterial nanocellulose / kaempferol / chitosan composite hemostatic material.
[0144] Embodiment 13
[0145] (1) Komagataeibacterxylinus ATCC 23770 was used as the bacterial strain. After being cultured in a liquid culture medium at a constant temperature for 10 days, the bacterial nanocellulose membrane was taken out and placed in a sodium hydroxide solution. After being treated in a water bath at 80°C for 2 h, the membrane was taken out and rinsed with deionized water. This process was repeated 8 times and then the membrane was soaked in deionized water until neutral to obtain the bacterial nanocellulose membrane.
[0146] (2) Weigh 300 g of the purified bacterial nanocellulose membrane, cut it into pieces, and then break it up in a high-speed homogenizer to form a bacterial nanocellulose suspension.
[0147] (3) 1L of bacterial nanocellulose suspension obtained in step (2) (solid content is 1%) is oxidized at room temperature using a TEMPO / NaBr / NaClO mixed oxidation system, with 0.16g of TEMPO and 1.03g of NaBr. 150mL of 10% NaClO solution is added to start the reaction. The pH of the reaction system is maintained at 10±0.5 by dripping 0.5M NaOH solution until no more NaOH solution is consumed, and then anhydrous ethanol of the same volume of NaClO is added to terminate the oxidation reaction. The obtained product is centrifuged, rinsed, dialyzed, compounded according to a solid content of 1%, sterilized under high pressure, and stored at 4°C. The degree of carboxyl oxidation of the TEMPO-oxidized bacterial nanocellulose suspension measured by conductivity titration is 23%.
[0148] (4) Take 10 mL of anhydrous ethanol and dilute to 1 L with deionized water to prepare an ethanol-water solution.
[0149] (5) Weigh 0.5 g of kaempferol and fully dissolve it in 100 mL of the ethanol aqueous solution prepared in step (4) to form a kaempferol solution with a final concentration of 0.5%.
[0150] (6) Weigh 1 g of chitosan (15 kDa) and fully dissolve it in 100 mL of 0.1 M glacial acetic acid aqueous solution to form a chitosan dilute acid solution with a final concentration of 1%.
[0151] (7) Weigh 5 g of ammonium persulfate and fully dissolve it in 100 mL of deionized water to form an ammonium persulfate aqueous solution with a final concentration of 5%. (8) According to the mass ratio of oxidized bacterial nanocellulose: chitosan = 2:1, take 10 mL of the chitosan dilute acid solution prepared in step (6) and dropwise add it into the beaker containing 20 mL of the oxidized bacterial nanocellulose suspension in step (3), stirring while adding, and react for 30 minutes.
[0152] (9) Take 1 mL of the ammonium persulfate aqueous solution prepared in step (7) and add it dropwise to the mixed solution of oxidized bacterial nanocellulose and chitosan in step (8), stirring while adding dropwise, and react for 30 minutes.
[0153] (10) 20 mL of the kaempferol solution prepared in step (5) was added dropwise to 31 mL of the oxidized bacterial nanocellulose suspension prepared in step (9). After reacting for 1 hour, the product was repeatedly centrifuged and rinsed, and finally freeze-dried to obtain an oxidized bacterial nanocellulose / kaempferol / chitosan (ammonium persulfate) composite hemostatic material.
[0154] Embodiment 14
[0155] (1) Komagataeibacterxylinus ATCC 23770 was used as the bacterial strain. After being cultured in a liquid culture medium at a constant temperature for 10 days, the bacterial nanocellulose membrane was taken out and placed in a sodium hydroxide solution. After being treated in a water bath at 80°C for 2 h, it was taken out and rinsed with deionized water. This process was repeated 8 times and then soaked in deionized water until neutral to obtain a bacterial nanocellulose membrane.
[0156] (2) Weigh 300 g of the purified bacterial nanocellulose membrane, cut it into pieces, and then break it up in a high-speed homogenizer to form a bacterial nanocellulose suspension.
[0157] (3) 1L of bacterial nanocellulose suspension obtained in step (2) (solid content is 1%) is oxidized at room temperature using a TEMPO / NaBr / NaClO mixed oxidation system, with 0.16g of TEMPO and 1.03g of NaBr. 150mL of 10% NaClO solution is added to start the reaction. The pH of the reaction system is maintained at 10±0.5 by dripping 0.5M NaOH solution until no more NaOH solution is consumed, and then anhydrous ethanol of the same volume of NaClO is added to terminate the oxidation reaction. The obtained product is centrifuged, rinsed, dialyzed, compounded according to a solid content of 1%, sterilized under high pressure, and stored at 4°C. The degree of carboxyl oxidation of the TEMPO-oxidized bacterial nanocellulose suspension measured by conductivity titration is 23%.
[0158] (4) Take 10 mL of anhydrous ethanol and dilute to 1 L with deionized water to prepare an ethanol-water solution.
[0159] (5) Weigh 0.5 g of apigenin and fully dissolve it in 100 mL of the ethanol aqueous solution prepared in step (4) to form an apigenin solution with a final concentration of 0.5%.
[0160] (6) Take 20 mL of the apigenin solution prepared in step (5) and add it dropwise to 20 mL of the oxidized bacterial nanocellulose suspension prepared in step (3). After reacting for 30 minutes, the product is repeatedly centrifuged and rinsed, and finally freeze-dried to obtain an oxidized bacterial nanocellulose / apigenin composite hemostatic material.
[0161] Embodiment 15
[0162] (1) Komagataeibacterxylinus ATCC 23770 was used as the bacterial strain. After being cultured in a liquid culture medium at a constant temperature for 10 days, the bacterial nanocellulose membrane was taken out and placed in a sodium hydroxide solution. After being treated in a water bath at 80°C for 2 h, it was taken out and rinsed with deionized water. This process was repeated 8 times and then soaked in deionized water until neutral to obtain a bacterial nanocellulose membrane.
[0163] (2) Weigh 300 g of the purified bacterial nanocellulose membrane, cut it into pieces, and then break it up in a high-speed homogenizer to form a bacterial nanocellulose suspension.
[0164] (3) 1L of bacterial nanocellulose suspension obtained in step (2) (solid content is 1%) is oxidized at room temperature using a TEMPO / NaBr / NaClO mixed oxidation system, with 0.16g of TEMPO and 1.03g of NaBr. 150mL of 10% NaClO solution is added to start the reaction. The pH of the reaction system is maintained at 10±0.5 by dripping 0.5M NaOH solution until no more NaOH solution is consumed, and then anhydrous ethanol of the same volume of NaClO is added to terminate the oxidation reaction. The obtained product is centrifuged, rinsed, dialyzed, compounded according to a solid content of 1%, sterilized under high pressure, and stored at 4°C. The degree of carboxyl oxidation of the TEMPO-oxidized bacterial nanocellulose suspension measured by conductivity titration is 23%.
[0165] (4) Take 10 mL of anhydrous ethanol and dilute to 1 L with deionized water to prepare an ethanol-water solution.
[0166] (5) Weigh 0.5 g of apigenin and fully dissolve it in 100 mL of the ethanol aqueous solution prepared in step (4) to form an apigenin solution with a final concentration of 0.5%.
[0167] (6) Weigh 1 g of chitosan (15 kDa) and fully dissolve it in 100 mL of 0.1 M glacial acetic acid aqueous solution to form a chitosan dilute acid solution with a final concentration of 1%.
[0168] (7) According to the mass ratio of oxidized bacterial nanocellulose: chitosan = 2:1, take 10 mL of the chitosan dilute acid solution prepared in step (6) and dropwise add it into the beaker containing 20 mL of the oxidized bacterial nanocellulose suspension in step (3), stirring while adding, and react for 30 minutes.
[0169] (8) Take 20 mL of the apigenin solution prepared in step (5) and add it dropwise to 30 mL of the oxidized bacterial nanocellulose suspension prepared in step (7). After reacting for 1 hour, the product is repeatedly centrifuged and rinsed, and finally freeze-dried to obtain an oxidized bacterial nanocellulose / apigenin / chitosan composite hemostatic material.
[0170] Example 16
[0171] (1) Komagataeibacterxylinus ATCC 23770 was used as the bacterial strain. After being cultured in a liquid culture medium at a constant temperature for 10 days, the bacterial nanocellulose membrane was taken out and placed in a sodium hydroxide solution. After being treated in a water bath at 80°C for 2 h, it was taken out and rinsed with deionized water. This process was repeated 8 times and then soaked in deionized water until neutral to obtain a bacterial nanocellulose membrane.
[0172] (2) Weigh 300 g of the purified bacterial nanocellulose membrane, cut it into pieces, and then break it up in a high-speed homogenizer to form a bacterial nanocellulose suspension.
[0173] (3) 1L of bacterial nanocellulose suspension obtained in step (2) (solid content is 1%) is oxidized at room temperature using a TEMPO / NaBr / NaClO mixed oxidation system, with 0.16g of TEMPO and 1.03g of NaBr. 150mL of 10% NaClO solution is added to start the reaction. The pH of the reaction system is maintained at 10±0.5 by dripping 0.5M NaOH solution until no more NaOH solution is consumed, and then anhydrous ethanol of the same volume of NaClO is added to terminate the oxidation reaction. The obtained product is centrifuged, rinsed, dialyzed, compounded according to a solid content of 1%, sterilized under high pressure, and stored at 4°C. The degree of carboxyl oxidation of the TEMPO-oxidized bacterial nanocellulose suspension measured by conductivity titration is 23%.
[0174] (4) Take 10 mL of anhydrous ethanol and dilute to 1 L with deionized water to prepare an ethanol-water solution.
[0175] (5) Weigh 0.5 g of apigenin and fully dissolve it in 100 mL of the ethanol aqueous solution prepared in step (4) to form an apigenin solution with a final concentration of 0.5%.
[0176] (6) Weigh 1 g of chitosan (15 kDa) and fully dissolve it in 100 mL of 0.1 M glacial acetic acid aqueous solution to form a chitosan dilute acid solution with a final concentration of 1%.
[0177] (7) Weigh 5 g of ammonium persulfate and dissolve it in 100 mL of deionized water to form an aqueous solution of ammonium persulfate with a final concentration of 5%. (8) According to the mass ratio of oxidized bacterial nanocellulose: chitosan = 2:1, take 10 mL of the chitosan dilute acid solution prepared in step (6) and dropwise add it into the beaker containing 20 mL of the oxidized bacterial nanocellulose suspension in step (3), stirring while adding, and react for 30 minutes.
[0178] (9) Take 1 mL of the ammonium persulfate aqueous solution prepared in step (7) and add it dropwise to the mixed solution of oxidized bacterial nanocellulose and chitosan in step (8), stirring while adding dropwise, and react for 30 minutes.
[0179] (10) Take 20 mL of the apigenin solution prepared in step (5) and add it dropwise to 31 mL of the oxidized bacterial nanocellulose suspension prepared in step (9). After reacting for 1 hour, the product is repeatedly centrifuged and rinsed, and finally freeze-dried to obtain an oxidized bacterial nanocellulose / apigenin / chitosan (ammonium persulfate) composite hemostatic material.
[0180] Embodiment 17
[0181] (1) Komagataeibacterxylinus ATCC 23770 was used as the bacterial strain. After being cultured in a liquid culture medium at a constant temperature for 10 days, the bacterial nanocellulose membrane was taken out and placed in a sodium hydroxide solution. After being treated in a water bath at 80°C for 2 h, the membrane was taken out and rinsed with deionized water. This process was repeated 8 times and then the membrane was soaked in deionized water until neutral to obtain the bacterial nanocellulose membrane.
[0182] (2) Weigh 300 g of the purified bacterial nanocellulose membrane, cut it into pieces, and then break it up in a high-speed homogenizer to form a bacterial nanocellulose suspension.
[0183] (3) 1L of bacterial nanocellulose suspension obtained in step (2) (solid content is 1%) is oxidized at room temperature using a TEMPO / NaBr / NaClO mixed oxidation system, with 0.16g of TEMPO and 1.03g of NaBr. 150mL of 10% NaClO solution is added to start the reaction. The pH of the reaction system is maintained at 10±0.5 by dripping 0.5M NaOH solution until no more NaOH solution is consumed, and then anhydrous ethanol of the same volume of NaClO is added to terminate the oxidation reaction. The obtained product is centrifuged, rinsed, dialyzed, compounded according to a solid content of 1%, sterilized under high pressure, and stored at 4°C. The degree of carboxyl oxidation of the TEMPO-oxidized bacterial nanocellulose suspension measured by conductivity titration is 23%.
[0184] (4) Take 10 mL of anhydrous ethanol and dilute to 1 L with deionized water to prepare an ethanol-water solution.
[0185] (5) Weigh 0.5 g of resveratrol and fully dissolve it in 100 mL of the ethanol aqueous solution prepared in step (4) to form a resveratrol solution with a final concentration of 0.5%.
[0186] (6) Take 20 mL of the resveratrol solution prepared in step (5) and add it dropwise to 20 mL of the oxidized bacterial nanocellulose suspension prepared in step (3). After reacting for 30 minutes, the product is repeatedly centrifuged and rinsed, and finally freeze-dried to obtain an oxidized bacterial nanocellulose / resveratrol composite hemostatic material.
[0187] Embodiment 18
[0188] (1) Komagataeibacterxylinus ATCC 23770 was used as the bacterial strain. After being cultured in a liquid culture medium at a constant temperature for 10 days, the bacterial nanocellulose membrane was taken out and placed in a sodium hydroxide solution. After being treated in a water bath at 80°C for 2 h, it was taken out and rinsed with deionized water. This process was repeated 8 times and then soaked in deionized water until neutral to obtain a bacterial nanocellulose membrane.
[0189] (2) Weigh 300 g of the purified bacterial nanocellulose membrane, cut it into pieces, and then break it up in a high-speed homogenizer to form a bacterial nanocellulose suspension.
[0190] (3) 1L of bacterial nanocellulose suspension obtained in step (2) (solid content is 1%) is oxidized at room temperature using a TEMPO / NaBr / NaClO mixed oxidation system, with 0.16g of TEMPO and 1.03g of NaBr. 150mL of 10% NaClO solution is added to start the reaction. The pH of the reaction system is maintained at 10±0.5 by dripping 0.5M NaOH solution until no more NaOH solution is consumed, and then anhydrous ethanol of the same volume of NaClO is added to terminate the oxidation reaction. The obtained product is centrifuged, rinsed, dialyzed, compounded according to a solid content of 1%, sterilized under high pressure, and stored at 4°C. The degree of carboxyl oxidation of the TEMPO-oxidized bacterial nanocellulose suspension measured by conductivity titration is 23%.
[0191] (4) Take 10 mL of anhydrous ethanol and dilute to 1 L with deionized water to prepare an ethanol-water solution.
[0192] (5) Weigh 0.5 g of resveratrol and fully dissolve it in 100 mL of the ethanol aqueous solution prepared in step (4) to form a resveratrol solution with a final concentration of 0.5%.
[0193] (6) Weigh 1 g of chitosan (15 kDa) and fully dissolve it in 100 mL of 0.1 M glacial acetic acid aqueous solution to form a chitosan dilute acid solution with a final concentration of 1%.
[0194] (7) According to the mass ratio of oxidized bacterial nanocellulose: chitosan = 2:1, take 10 mL of the chitosan dilute acid solution prepared in step (6) and dropwise add it into the beaker containing 20 mL of the oxidized bacterial nanocellulose suspension in step (3), stirring while adding, and react for 30 minutes.
[0195] (8) Take 20 mL of the resveratrol solution prepared in step (5) and add it dropwise into 30 mL of the oxidized bacterial nanocellulose suspension prepared in step (7). After reacting for 1 hour, the product is repeatedly centrifuged and rinsed, and finally freeze-dried to obtain an oxidized bacterial nanocellulose / resveratrol / chitosan composite hemostatic material.
[0196] Embodiment 19
[0197] (1) Komagataeibacterxylinus ATCC 23770 was used as the bacterial strain. After being cultured in a liquid culture medium at a constant temperature for 10 days, the bacterial nanocellulose membrane was taken out and placed in a sodium hydroxide solution. After being treated in a water bath at 80°C for 2 h, the membrane was taken out and rinsed with deionized water. This process was repeated 8 times and then the membrane was soaked in deionized water until neutral to obtain the bacterial nanocellulose membrane.
[0198] (2) Weigh 300 g of the purified bacterial nanocellulose membrane, cut it into pieces, and then break it up in a high-speed homogenizer to form a bacterial nanocellulose suspension.
[0199] (3) 1L of bacterial nanocellulose suspension obtained in step (2) (solid content is 1%) is oxidized at room temperature using a TEMPO / NaBr / NaClO mixed oxidation system, with 0.16g of TEMPO and 1.03g of NaBr. 150mL of 10% NaClO solution is added to start the reaction. The pH of the reaction system is maintained at 10±0.5 by dripping 0.5M NaOH solution until no more NaOH solution is consumed, and then anhydrous ethanol of the same volume of NaClO is added to terminate the oxidation reaction. The obtained product is centrifuged, rinsed, dialyzed, compounded according to a solid content of 1%, sterilized under high pressure, and stored at 4°C. The degree of carboxyl oxidation of the TEMPO-oxidized bacterial nanocellulose suspension measured by conductivity titration is 23%.
[0200] (4) Take 10 mL of anhydrous ethanol and dilute to 1 L with deionized water to prepare an ethanol-water solution.
[0201] (5) Weigh 0.5 g of resveratrol and fully dissolve it in 100 mL of the ethanol aqueous solution prepared in step (4) to form a resveratrol solution with a final concentration of 5 mg / mL.
[0202] (6) Weigh 1 g of chitosan (15 kDa) and fully dissolve it in 100 mL of 0.1 M glacial acetic acid aqueous solution to form a chitosan dilute acid solution with a final concentration of 1%.
[0203] (7) Weigh 5 g of ammonium persulfate and dissolve it in 100 mL of deionized water to form an aqueous solution of ammonium persulfate with a final concentration of 5%. (8) According to the mass ratio of oxidized bacterial nanocellulose: chitosan = 2:1, take 10 mL of the chitosan dilute acid solution prepared in step (6) and dropwise add it into the beaker containing 20 mL of the oxidized bacterial nanocellulose suspension in step (3), stirring while adding, and react for 30 minutes.
[0204] (9) Take 1 mL of the ammonium persulfate aqueous solution prepared in step (7) and add it dropwise to the mixed solution of oxidized bacterial nanocellulose and chitosan in step (8), stirring while adding dropwise, and react for 30 minutes.
[0205] (10) Take 20 mL of the resveratrol solution prepared in step (5) and add it dropwise into 31 mL of the oxidized bacterial nanocellulose suspension prepared in step (9). After reacting for 1 hour, the product is repeatedly centrifuged and rinsed, and finally freeze-dried to obtain an oxidized bacterial nanocellulose / resveratrol / chitosan (ammonium persulfate) composite hemostatic material.
[0206] Comparative Example 1
[0207] (1) Komagataeibacterxylinus ATCC 23770 was used as the bacterial strain. After being cultured in a liquid culture medium at a constant temperature for 10 days, the bacterial nanocellulose membrane was taken out and placed in a sodium hydroxide solution. After being treated in a water bath at 80°C for 2 h, it was taken out and rinsed with deionized water. This process was repeated 8 times and then soaked in deionized water until neutral to obtain a bacterial nanocellulose membrane.
[0208] (2) Weigh 300 g of the purified bacterial nanocellulose membrane, cut it into pieces, and then break it up in a high-speed homogenizer to form a bacterial nanocellulose suspension.
[0209] (3) 1L of bacterial nanocellulose suspension (solid content 1%) obtained in step (2) was oxidized at room temperature by TEMPO / NaBr / NaClO mixed oxidation system, with 0.08g of TEMPO and 1.03g of NaBr. 150mL of 10% NaClO solution was added to start the reaction. The pH of the reaction system was maintained at 10±0.5 by dropwise addition of 0.5M NaOH solution, and when no more NaOH solution was consumed, anhydrous ethanol of the same volume of NaClO was added to terminate the oxidation reaction. The obtained product was centrifuged, rinsed, dialyzed, compounded according to a solid content of 1%, and sterilized by high pressure, and then stored at 4°C. The degree of carboxyl oxidation of the TEMPO-oxidized bacterial nanocellulose suspension was 10% as measured by conductivity titration.
[0210] (4) freeze-drying the oxidized bacterial nanocellulose suspension obtained in step (3) to finally obtain the oxidized bacterial nanocellulose hemostatic material.
[0211] Comparative Example 2
[0212] (1) Komagataeibacterxylinus ATCC 23770 was used as the bacterial strain. After being cultured in a liquid culture medium at a constant temperature for 10 days, the bacterial nanocellulose membrane was taken out and placed in a sodium hydroxide solution. After being treated in a water bath at 80°C for 2 h, it was taken out and rinsed with deionized water. This process was repeated 8 times and then soaked in deionized water until neutral to obtain a bacterial nanocellulose membrane.
[0213] (2) Weigh 300 g of the purified bacterial nanocellulose membrane, cut it into pieces, and then break it up in a high-speed homogenizer to form a bacterial nanocellulose suspension.
[0214] (3) 1L of bacterial nanocellulose suspension (solid content 1%) obtained in step (2) was oxidized at room temperature by TEMPO / NaBr / NaClO mixed oxidation system, with 0.30g of TEMPO and 1.03g of NaBr. 150mL of 10% NaClO solution was added to start the reaction. The pH of the reaction system was maintained at 10±0.5 by dripping 0.5M NaOH solution until no more NaOH solution was consumed, and anhydrous ethanol of the same volume of NaClO was added to terminate the oxidation reaction. The obtained product was centrifuged, rinsed, dialyzed, compounded according to a solid content of 1%, and sterilized by high pressure, and then stored at 4°C. The degree of carboxyl oxidation of the TEMPO-oxidized bacterial nanocellulose suspension was 50% as measured by conductivity titration.
[0215] (4) freeze-drying the oxidized bacterial nanocellulose suspension obtained in step (3) to finally obtain the oxidized bacterial nanocellulose hemostatic material.
[0216] Comparative Example 3
[0217] (1) Komagataeibacter xylinus ATCC 23770 was used as the bacterial strain. After being cultured in a liquid culture medium at a constant temperature for 10 days, the bacterial nanocellulose membrane was taken out and placed in a sodium hydroxide solution. After being treated in a water bath at 80°C for 2 h, the membrane was taken out and rinsed with deionized water. This process was repeated 8 times and then the membrane was soaked in deionized water until neutral to obtain the bacterial nanocellulose membrane.
[0218] (2) Weigh 300 g of the purified bacterial nanocellulose membrane, cut it into pieces, and then break it up in a high-speed homogenizer to form a bacterial nanocellulose suspension.
[0219] (3) 1L of bacterial nanocellulose suspension obtained in step (2) (solid content of 1%) was oxidized at room temperature by a TEMPO / NaBr / NaClO mixed oxidation system, with 0.16g of TEMPO and 1.03 / g of NaBr. 150mL of 10% NaClO solution was added to start the reaction. The pH of the reaction system was maintained at 10±0.5 by dripping 0.5M NaOH solution until no more NaOH solution was consumed, and anhydrous ethanol of the same volume of NaClO was added to terminate the oxidation reaction. The obtained product was centrifuged, rinsed, dialyzed, compounded according to a solid content of 1%, and sterilized by high pressure, and then stored at 4°C. The degree of carboxyl oxidation of the TEMPO-oxidized bacterial nanocellulose suspension was measured by conductivity titration to be 23%.
[0220] (4) Weigh 1 g of chitosan (15 kDa) and fully dissolve it in 100 mL of 0.1 M glacial acetic acid aqueous solution to form a chitosan dilute acid solution with a final concentration of 1%.
[0221] (5) According to the mass ratio of oxidized bacterial nanocellulose: chitosan = 1:1, take 10 mL of the chitosan dilute acid solution prepared in step (6) and dropwise add it into the beaker of 10 mL of the oxidized bacterial nanocellulose suspension in step (3), stirring while adding, and react for 30 minutes. After reacting for 1 hour, the product is repeatedly centrifuged and rinsed, and finally freeze-dried to obtain an oxidized bacterial nanocellulose / chitosan composite hemostatic material.
[0222] Comparative Example 4
[0223] (1) Komagataeibacter xylinus ATCC 23770 was used as the bacterial strain. After being cultured in a liquid culture medium at a constant temperature for 10 days, the bacterial nanocellulose membrane was taken out and placed in a sodium hydroxide solution. After being treated in a water bath at 80°C for 2 h, it was taken out and rinsed with deionized water. This process was repeated 8 times and then soaked in deionized water until neutral to obtain a bacterial nanocellulose membrane.
[0224] (2) Weigh 300 g of the purified bacterial nanocellulose membrane, cut it into pieces, and then break it up in a high-speed homogenizer to form a bacterial nanocellulose suspension.
[0225] (3) 1L of bacterial nanocellulose suspension (solid content 1%) obtained in step (2) was oxidized at room temperature by TEMPO / NaBr / NaClO mixed oxidation system, with 0.16g of TEMPO and 1.03g of NaBr. 150mL of 10% NaClO solution was added to start the reaction. The pH of the reaction system was maintained at 10±0.5 by dripping 0.5M NaOH solution until no more NaOH solution was consumed, and anhydrous ethanol of the same volume of NaClO was added to terminate the oxidation reaction. The obtained product was centrifuged, rinsed, dialyzed, compounded according to a solid content of 1%, and sterilized by high pressure, and then stored at 4°C. The degree of carboxyl oxidation of the TEMPO-oxidized bacterial nanocellulose suspension was measured by conductivity titration to be 23%.
[0226] (4) Weigh 1 g of chitosan (15 kDa) and fully dissolve it in 100 mL of 0.1 M glacial acetic acid aqueous solution to form a chitosan dilute acid solution with a final concentration of 1%.
[0227] (5) According to the mass ratio of oxidized bacterial nanocellulose: chitosan = 3:1, take 10 mL of the chitosan dilute acid solution prepared in step (6) and dropwise add it into the beaker of 30 mL of the oxidized bacterial nanocellulose suspension in step (3), stirring while adding, and react for 30 minutes. After reacting for 1 hour, the product is repeatedly centrifuged and rinsed, and finally freeze-dried to obtain an oxidized bacterial nanocellulose / chitosan composite hemostatic material.
[0228] Comparative Example 5
[0229] (1) Komagataeibacter xylinus ATCC 23770 was used as the bacterial strain. After being cultured in a liquid culture medium at a constant temperature for 10 days, the bacterial nanocellulose membrane was taken out and placed in a sodium hydroxide solution. After being treated in a water bath at 80°C for 2 h, the membrane was taken out and rinsed with deionized water. This process was repeated 8 times and then the membrane was soaked in deionized water until neutral to obtain the bacterial nanocellulose membrane.
[0230] (2) Weigh 300 g of the purified bacterial nanocellulose membrane, cut it into pieces, and then break it up in a high-speed homogenizer to form a bacterial nanocellulose suspension.
[0231] (3) 1L of bacterial nanocellulose suspension (solid content 1%) obtained in step (2) was oxidized at room temperature by TEMPO / NaBr / NaClO mixed oxidation system, with 0.16g of TEMPO and 1.03g of NaBr. 150mL of 10% NaClO solution was added to start the reaction. The pH of the reaction system was maintained at 10±0.5 by dripping 0.5M NaOH solution until no more NaOH solution was consumed, and anhydrous ethanol of the same volume of NaClO was added to terminate the oxidation reaction. The obtained product was centrifuged, rinsed, dialyzed, compounded according to a solid content of 1%, and sterilized by high pressure, and then stored at 4°C. The degree of carboxyl oxidation of the TEMPO-oxidized bacterial nanocellulose suspension was measured by conductivity titration to be 23%.
[0232] (4) Weigh 1 g of chitosan (1 kDa) and fully dissolve it in 100 mL of 0.1 M glacial acetic acid aqueous solution to form a chitosan dilute acid solution with a final concentration of 1%.
[0233] (5) According to the mass ratio of oxidized bacterial nanocellulose: chitosan = 2:1, take 10 mL of the chitosan dilute acid solution prepared in step (6) and dropwise add it into the beaker of 20 mL of the oxidized bacterial nanocellulose suspension in step (3), stirring while adding, and react for 30 minutes. After reacting for 1 hour, the product is repeatedly centrifuged and rinsed, and finally freeze-dried to obtain an oxidized bacterial nanocellulose / chitosan composite hemostatic material.
[0234] Comparative Example 6
[0235] (1) Komagataeibacter xylinus ATCC 23770 was used as the bacterial strain. After being cultured in a liquid culture medium at a constant temperature for 10 days, the bacterial nanocellulose membrane was taken out and placed in a sodium hydroxide solution. After being treated in a water bath at 80°C for 2 h, the membrane was taken out and rinsed with deionized water. This process was repeated 8 times and then the membrane was soaked in deionized water until neutral to obtain the bacterial nanocellulose membrane.
[0236] (2) Weigh 300 g of the purified bacterial nanocellulose membrane, cut it into pieces, and then break it up in a high-speed homogenizer to form a bacterial nanocellulose suspension.
[0237] (3) 1L of bacterial nanocellulose suspension (solid content 1%) obtained in step (2) was oxidized at room temperature by TEMPO / NaBr / NaClO mixed oxidation system, with 0.16g of TEMPO and 1.03g of NaBr. 150mL of 10% NaClO solution was added to start the reaction. The pH of the reaction system was maintained at 10±0.5 by dripping 0.5M NaOH solution until no more NaOH solution was consumed, and anhydrous ethanol of the same volume of NaClO was added to terminate the oxidation reaction. The obtained product was centrifuged, rinsed, dialyzed, compounded according to a solid content of 1%, and sterilized by high pressure, and then stored at 4°C. The degree of carboxyl oxidation of the TEMPO-oxidized bacterial nanocellulose suspension was measured by conductivity titration to be 23%.
[0238] (4) Weigh 1 g of chitosan (30 kDa) and fully dissolve it in 100 mL of 0.1 M glacial acetic acid aqueous solution to form a chitosan dilute acid solution with a final concentration of 1%.
[0239] (5) According to the mass ratio of oxidized bacterial nanocellulose: chitosan = 2:1, take 10 mL of the chitosan dilute acid solution prepared in step (6) and dropwise add it into the beaker of 20 mL of the oxidized bacterial nanocellulose suspension in step (3), stirring while adding, and react for 30 minutes. After reacting for 1 hour, the product is repeatedly centrifuged and rinsed, and finally freeze-dried to obtain an oxidized bacterial nanocellulose / chitosan composite hemostatic material.
[0240] Table 1 Antibacterial test results of the materials prepared in Examples 1-19 and Comparative Examples 1-6 against three kinds of bacteria
[0241]
[0242]
[0243] Note: Sterile gauze is the control group, and the test method is based on ISO-20743-2007.
[0244] It can be seen from Table 1 that OBC has basic antibacterial properties. It can be seen from Example 1 and Comparative Examples 1 and 2 that the carboxyl group of OBC does not play a major antibacterial role. It can be seen from Examples 3, 6, 9, 12, 15, 18 and Comparative Examples 3-6 that chitosan plays a major antibacterial role, and the content of OBC and the molecular weight of chitosan have little effect on it. The concentration of natural anti-inflammatory small molecules in the composite material cannot meet the antibacterial performance. It can be seen from Comparative Examples 3-4 that only relying on hydrogen bonds or electrostatic interactions can only adsorb a small part of chitosan on the surface of the cellulose network, and a large amount of free chitosan will be washed and removed in the next process. Combined with Example 4, it can be seen that ammonium persulfate can further deposit free chitosan on the surface of cellulose, increasing the utilization rate of raw materials. The antibacterial rate of the material after the surface of Example 2-19 is composited with a hydroxyl-containing small molecule natural anti-inflammatory compound is significantly improved. The further introduction of chitosan and ammonium persulfate can increase the antibacterial rate of the material to three bacteria to more than 95%. The excellent antibacterial properties make these materials have the potential for clinical application.
[0245] Depend on Figure 3 It can be seen that the prepared sponge samples all have a uniformly distributed macroporous structure. Ammonium persulfate will cause the loose chitosan fibers to aggregate and produce a dense lamellar structure on the surface of the material, which makes the material have a higher porosity and specific surface area.
[0246] Depend on Figure 4 It could be demonstrated that OBC has limited procoagulant effect in vitro, whereas chitosan could promote this process.
[0247] Figure 5 These are the hemolysis rate test results of Examples 1 to 19. Therefore, the hemolysis rates of the materials are all lower than 5%, and they have good blood compatibility.
[0248] Depend on Figure 6 It can be seen that OBC can provide an adhesion surface for red blood cells, and the introduction of hydroxyl-containing small molecule natural anti-inflammatory compounds and chitosan can increase the number of red blood cells that adhere.
[0249] Figure 7 The macroscopic hemostasis results obtained in Examples 1-4 using the SD rat liver trauma model and rat tail amputation model showed that OBC absorbed a large amount of blood, resulting in structural collapse. The structure of OBC / GA / CS-APS was relatively intact after hemostasis, and the amount of blood absorbed was lower than that of the other groups.
[0250] Figure 8 The blood absorption amounts recorded for the animal models of Examples 1-4, the blood absorption amounts for the liver trauma model and the blood absorption amounts for the rat tail docking model were 231 mg / 265 mg, 133 mg / 65 mg, 71 mg / 52 mg and 30 mg / 25 mg, respectively.
[0251] Fig. 9The hemostasis times recorded for the animal models of Examples 1-4, the hemostasis times for the liver trauma model and the rat tail amputation model were 291s / 245s, 272s / 256s, 233s / 181s and 130s / 119s, respectively.
[0252] Fig.10 The test results of the hydroxyl radical scavenging rate of Examples 1-19 show that the small molecule natural anti-inflammatory compounds containing hydroxyl groups play a major antioxidant role, and only when their concentration reaches a certain value can they have a significant ability to scavenge hydroxyl radicals.
[0253] Fig.11 HE and Masson staining of subcutaneous embedding materials of SD rats. We can see that there are a large number of inflammatory cells in the OBC sections, while the number of inflammatory cells in the OBC / GA sections is significantly reduced. A large number of tissue cells grow around the OBC / GA / CS and OBC / GA / CS-APS sponges, and the number of inflammatory cells is relatively small, especially the number of cells proliferating on the surface of OBC / GA / CS-APS is much greater than that of sponges in other groups. After 28 days of embedding, there are still obvious cellulose residues in the OBC, OBC / GA and OBC / GA / CS sections, but no abnormal cell proliferation occurs. Relatively speaking, only some residual cellulose fragments can be observed in the OBC / GA / CS-APS group. On the whole, tissue repair is relatively complete, the observed cells are fully spread, and there are no obvious growing and dividing cells.
[0254] The present invention skillfully combines the two materials without destroying the original structure, and the obtained composite material has broad-spectrum antibacterial properties, excellent blood compatibility and excellent hemostatic properties. It can play an anti-inflammatory and antioxidant role, promote tissue healing, and accelerate the absorption of the material in the body. It has great potential as a hemostatic material in clinical practice.
Claims
1. An oxidized nanocellulose composite material, characterized in that: The oxidized nanocellulose composite material comprises a matrix and a hydroxyl-containing small molecule natural anti-inflammatory compound loaded on the matrix; wherein the matrix is an oxidized nanocellulose nanofiber network, a composite material of an oxidized nanocellulose nanonetwork and chitosan, or a composite material of an oxidized nanocellulose nanonetwork and chitosan aggregated by ammonium persulfate.
2. The oxidized bacterial nanocellulose composite material according to claim 1, characterized in that: The oxidized nanocellulose is oxidized bacterial nanocellulose; the hydroxyl-containing small molecule natural anti-inflammatory compound is one or more of gallic acid, salicylic acid, quercetin, kaempferol, apigenin, and resveratrol; and the molecular weight of the chitosan is 1 kDa-30 kDa.
3. A method for preparing an oxidized nanocellulose composite material, comprising method 1, method 2 or method 3, specifically as follows: Method 1: adding a hydroxyl-containing small molecule natural anti-inflammatory compound solution to oxidized nanocellulose, reacting, centrifuging and washing, and freeze-drying to obtain an oxidized nanocellulose composite material; Method 2: adding chitosan solution to oxidized nanocellulose, reacting, then adding hydroxyl-containing small molecule natural anti-inflammatory compound solution, reacting, centrifuging and washing, freeze-drying, to obtain oxidized nanocellulose composite material; Method 3: Add chitosan solution to oxidized nanocellulose, react, then add ammonium persulfate solution, react, then add hydroxyl-containing small molecule natural anti-inflammatory compound solution, react, centrifuge and wash, freeze-dry, and obtain an oxidized nanocellulose composite material.
4. The preparation method according to claim 3, characterized in that: The oxidized nanocellulose in method 1, method 2 or method 3 is oxidized bacterial nanofiber.
5. The preparation method according to claim 4, characterized in that: The preparation process of the oxidized bacterial nanocellulose suspension comprises: breaking up the bacterial nanocellulose membrane by a homogenizer, oxidizing at room temperature by using a TEMPO / NaBr / NaClO mixed oxidation system, centrifugation washing and dialysis.
6. The preparation method according to claim 4, characterized in that: The oxidation degree of the oxidized bacterial nanocellulose is 10%-50%.
7. The preparation method according to claim 3, characterized in that: The solvent of the hydroxyl-containing small molecule natural anti-inflammatory compound solution in methods 1 to 3 is water or ethanol aqueous solution; the concentration of the hydroxyl-containing small molecule natural anti-inflammatory compound solution is 0.1wt%-1wt%.
8. The preparation method according to claim 3, characterized in that: In methods 1 to 3, the mass ratio of the hydroxyl-containing small molecule natural anti-inflammatory compound to the oxidized bacterial nanocellulose is 1:1-1:5; in methods 2 to 3, the mass ratio of the oxidized bacterial nanocellulose to chitosan is 1:1-3:1; in method 3, the mass ratio of ammonium persulfate to chitosan is 1:1-1:
5.
9. The preparation method according to claim 3, characterized in that: The addition method in methods 1 to 3 is dropwise addition; The reaction time in method 1 is 0.5-6h; In the method 2, the chitosan solution is added to the oxidized nanocellulose, and the reaction is carried out for 0.5-5 hours, and then the hydroxyl-containing small molecule natural anti-inflammatory compound solution is added and the reaction is carried out for 0.5-6 hours; In the method 3, the chitosan solution is added to the oxidized nanocellulose, reacted for 0.5-5 hours, then the ammonium persulfate solution is added, reacted for 0.5-3 hours, and then the hydroxyl-containing small molecule natural anti-inflammatory compound solution is added, reacted for 0.5-6 hours.
10. Use of the oxidized nanocellulose composite material according to any one of claims 1-2 in the preparation of hemostatic, antibacterial and healing-promoting materials.
Citation Information
Patent Citations
Method for preparing modified regenerated cellulose / alginate hemostatic composite material
CN104013991A
Preparation method of multi-wall carbon nano tube / chitosan / oxidized regenerated cellulose composite hemostatic material
CN105056284A
Preparation method of oxidized nano-cellulose / collagen composite sponge
CN105079886A
Novel degradable hemostatic material and preparing method thereof
CN110339391A